2009
DOI: 10.1021/ol901236s
|View full text |Cite
|
Sign up to set email alerts
|

Regio- and Stereoselective Synthesis of Multisubstituted Vinylsilanes via Zirconacycles

Abstract: A series of novel multisubstituted vinylsilanes are prepared regio- and stereoselectively by carbozirconation of various alkynylsilanes through zirconacycles such as zirconacyclopropenes and zirconacyclopentenes and the subsequent transformation of the formed alkenylzirconocene complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 35 publications
(41 reference statements)
1
18
0
Order By: Relevance
“…Within the same carbozirconation protocol, the addition of allyloxytrimethylsilane led to its rapid reaction with the intermediate zirconacyclopropene 288 to expand the The double arylation reaction (Scheme 10.98, path B) also proceeded in this case to form the desired product 294, albeit in low yield. It has been mentioned that the developed carbozirconation also has a potential application to the regio-and stereoselective synthesis of oligosubstituted alkenes [79]. A consistent extension of this work disclosing the application of the Negishi .…”
Section: Intermolecular Reactionssupporting
confidence: 71%
See 2 more Smart Citations
“…Within the same carbozirconation protocol, the addition of allyloxytrimethylsilane led to its rapid reaction with the intermediate zirconacyclopropene 288 to expand the The double arylation reaction (Scheme 10.98, path B) also proceeded in this case to form the desired product 294, albeit in low yield. It has been mentioned that the developed carbozirconation also has a potential application to the regio-and stereoselective synthesis of oligosubstituted alkenes [79]. A consistent extension of this work disclosing the application of the Negishi .…”
Section: Intermolecular Reactionssupporting
confidence: 71%
“…The formation of substituted alkenylsilanes by a carbometallation process was achieved by Nishihara et al [79]. When alkynylsilanes were treated with the Takahashi reagent [80], the reaction presumably afforded the intermediate zirconacyclopropene 288, which on hydrolysis or deuterolysis gave exclusively (Z)-alkenylsilanes 290 in moderate to good yields (Scheme 10.97).…”
Section: Intermolecular Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…E2 reaction), neither Hofmann (less-substituted olefins) [8] nor Saytzeff (more-substituted olefins) [9] elimination can perfectly control reaction selectivity with mixtures of structural isomers being obtained. Recently, our research group has demonstrated the usefulness of 1-alkynylboronates [10] and 1-alkynylsilanes [11] as applied to zirconium chemistry to afford a highly regio-and stereoselective syntheses of multisubstituted olefins. Herein, we describe a practical and versatile procedure for the formation of tri-and tetrasubstituted olefins bearing different b-hydrogen-containing alkyl groups by carbozirconation of 1-alkynylboronates and successive Negishi [12] and/or SuzukiMiyaura [13] cross-coupling reactions with high regio-and stereoselectivities (Scheme 1).…”
Section: Dedicated To Professor Tamejiro Hiyama On the Occasion Of Himentioning
confidence: 99%
“…[17] The regiochemistry of 2 a-2 e was confirmed by comparison of their spectroscopic data with those reported for authentic compounds [18] prepared by the reactions of 1-alkynylboronates with Takahashi reagent ([Cp 2 ZrCl 2 ]/2 EtMgBr), [19] as well as 1 H NMR spectra that show the presence of a highly shifted triplet with a small coupling constants (J = 1.5 Hz) in the double bond region (5.02-5.13 ppm), and is indicative of a hydrogen atom located geminal to the boron functionality. Alternately, the 11 organoboronic acids. [20] Although it has been reported that the Suzuki-Miyaura coupling of alkenylboronates with alkyl bromides possessing b-hydrogen atoms proceed at 60 8C, [21] the higher temperature caused undesired b-hydrogen elimination in our previously reported nickel-catalyzed crosscoupling of alkenylboronates with alkyl iodides.…”
Section: Dedicated To Professor Tamejiro Hiyama On the Occasion Of Himentioning
confidence: 99%